شیکردنەوەیەکی جوگرافی بۆ قەبارە و شێوازی نشینگە دێهاتیەکانی قەزای شارباژێڕ لەماوەی نێوان ساڵانی (2019-1957) - رشید, شیروان عمر; حمە, سروە جلال; سلیم, غریب علی (Sulaimani Journal for Humanities, 2022)
This research is entitled a geographical analysis for the size and pattern of rural settlements in Sharbazher district between (1957-2019), the aim of the research is to show the population distribution, ranking of the size and the current distribution pattern. Astronomically, Sharbazher district is located between the two latitudes (36°, 35°, 32-, 11=) of the north and the two longitudes (45°, 13-, 07=, and 45°, 49-, 26=) of the east. This has given the region special importance as it borders with Iran and five districts of Sulaimani province, so it has an important economic and commercial position, because it passes through several important ways and becomes a gateway for the exchange of goods between Iraq and Iran. Three trade caravans have passed through Sharbazher from east to west since ancient times. Administratively, the district currently consists of four sub districts Chwarta (Basne, Gapilon, Sitak, Zalan), with an area of (1211 km2). Depend on the aim, the research is divided into three main sections, (introduction of the study area, and geographical distribution of population, distribution of rural settlements according to size and distribution patterns). The study concluded that the rural settlements in the district have changed in size and pattern. It has decreased from 260 villages to 139, due to political, demographic and administrative changes in the region. This is despite the fact that the topography influence of the region has changed from time to time and from place to place. The Rural settlements have also shaped a clustered and scatter pattern due to the natural and human factors.
Keywords: Size; Pattern; Size Vallige; Rural; Sharbazher district